Determinación de la relación entre los diferentes tipos de forrajes con el porcentaje de sólidos totales en leche de vaca en Chao • La Libertad. - Rodriguez Guevara, Itala Mariell (2010)
The work of investigation was realised in the district of Ciao; province of Viru - the Freedom, with the aim of determining: The effect of different types from forages used in the feeding on the composition of milk in cows in the different stables from Ciao - the Freedom, to determine the percentage of total milk solids of cows of the locality of Ciao, to determine the effect of the different fodder species on the quality from milk of cow in the locality of Ciao. They analyzed the originating milk of 30 at random selected stables. For the milk analysis 6 samples by each stable in an amount removed from 100 ml Which were packaged in special and fillings in a box of tecnopor for their conservation and codified containers, soon to be sent for the respective analysis in the laboratory of the Nestlé of Chiclayo. They were processed using lactoscan. The used statistical design was Diseño of blocks completely at random (DBCA). The best total solid results were in the experimental treatments T. l. (11,59%) and T.3 (11,51 %) with respect to T.2 (11,41 %) and T.4 (11,16%), the best percentage offat presented /displayed T. l. (3,33%) followed ofT.3 (3,3%) wh~reas T.2 (3,25%) and T.4 (3,07%). Statistically the T.1 treatment surpasses to T. 3 (p<0.01). and these to T.2 and T.4. The best percentage ofproteins appeared in T.1 (2,85%) and T.3 (2,82%) with respect to T.2 (2,76%) and T.4 (2,68%). Also I determine that of the 30 evaluated stables; the feeding of 17 stables is with alfalfa like forage, 6 stables with alfalfa but sorghum, 4 stables with chala and 3 stables with sorghum. One concludes that in the majority of the stables of ciao the feeding it is with forage and few are those that they use to the sorghum like forage. As well as the greater percentage of total solids it was obtained in the stables whose feeding is with alfalfa.